Pemimpin Transformatif dalam Pendidikan Kristen - Marbun, Purim (Sekolah Tinggi Teologi IKAT Jakarta, 2020)
This paper aims to explain the essence of transformative leaders carried out by Christian leaders in the field of education both formal and informal. This research is based on the background of the problem of the minimal changes made by leaders due to competent competence. The research method used in this paper is a literature study by examining various literatures related to the topics discussed. Leadership basically explains a number of skills and abilities of leaders in carrying out leadership tasks. Specifically for Christian leaders, this task is done not with mere ability but based on gifts and talents given by God. The results of transformative leadership in education create breakthroughs, changes in values and systems and have an impact on themselves and the people they lead. and bring them to recognize the work of God in their lives and leadership. Abstract Tulisan ini bertujuan menjelaskan esensi dari pemimpin transformatif yang dilakukan oleh pemimpin kristen dalam bidang pendidikan baik formal maupun informal. Penelitian ini didasakan pada latar belakang masalah minimnya perubahan-perubahan yang dilakukan pemimpin disebabkan kompetensi yang tidak mumpuni. Metode penelitian yang digunakan dalam tulisan ini ialah studi kepustkaan dengan mengkaji berbagai literatur yang berkaitan dengan topik yang dibahas. Kepemimpinan pada dasarnya menjelaskan sejumlah kecakapan dan kemampuan pemimpin dalam menjalankan tugas-tugas kepemimpinan. Secara khusus bagi pemimpin Kristen, tugas ini dilakukan bukan dengan kemampuan semata melainkan berdasarkan karunia dan talenta yang diberikan Allah. Hasil kepemimpinan transformatif dalam pendidikan terciptanya terobosan, perubahan nilai dan sistem serta berdampak bagi diri sendiri dan orang yang yang dipimpinnya. dan membawa mereka mengakui karya Allah dalam hidup dan kepemimpinan mereka.